2007
DOI: 10.2214/ajr.07.2408
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Quadratus Femoris Muscle Tear: Another Cause of Hip Pain

Abstract: MRI is an important tool in assisting clinicians to make a correct diagnosis for the patient who presents with hip pain. Although quadratus femoris muscle tear is an uncommon injury, radiologists should be aware of this entity to assist with making a diagnosis that is usually unsuspected clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 5 publications
3
47
0
Order By: Relevance
“…As was true in our case, O'Brien and Bui-Mansfield (4) , in their study, found that non-surgical interventions were adequate for a good resolution in cases of hip pain due to inflammation of the quadratus femoris muscle.…”
Section: Ischiofemoral Impingementsupporting
confidence: 81%
“…As was true in our case, O'Brien and Bui-Mansfield (4) , in their study, found that non-surgical interventions were adequate for a good resolution in cases of hip pain due to inflammation of the quadratus femoris muscle.…”
Section: Ischiofemoral Impingementsupporting
confidence: 81%
“…There is no specific diagnostic clinical test for this disorder; however, clinicians should consider IFI when there is an increase in pain during maneuvers that impinge the muscle (1,7,8). Patients may also experience a snapping sensation, crepitation, or locking of the joint (3,6).…”
mentioning
confidence: 99%
“…Hip disorders being coexistent with QFMC make it difficult to establish an adequate clinical diagnosis. GTE and HSE were the first reported ipsilateral associated imaging findings in one patient (5). In the same report a contralateral stress fracture was observed in another patient.…”
Section: Associated Findingsmentioning
confidence: 66%
“…Subsequent MRI case studies also focused on the traumatic origin of QFMC (3)(4)(5). This QFMC was interpreted as the result of muscle strain or tearing of the QFM.…”
Section: Mechanisms Responsible For Qfmcmentioning
confidence: 99%